2007
DOI: 10.1177/030857590703100109
|View full text |Cite
|
Sign up to set email alerts
|

The Educational Outcomes of Young People 4–5 Years after Leaving Care: An Australian Perspective

Abstract: Townsend focus on the educational and employment pathways and outcomes for young people after leaving care in Australia, based on a longitudinal study of young people 'ageing' out of care in New South Wales. Consistent with the findings of other research on the educational performance and attainment of children and young people in care, the young people leaving care in this study were less likely to have completed their secondary schooling than others their age in the general population. Four to five years aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 18 publications
3
23
0
7
Order By: Relevance
“…Many authors also comment, that along with the stresses and strains felt by care givers and workers in the OOHC system and the poor attention paid to OOHC politically and academically, the national data indicates that we are continuing to fail to halt the rise of children coming into care, the rise in placement breakdown, poor reunification rates, poor educational outcomes, and the poor social and emotional health and wellbeing of children in care (Barber, 2001;Carter, 2004;Cashmore, Paxman, & Townsend, 2007). The National Standards for OOHC: Consultation Paper (2010) states that it is 'widely reported that children who have been placed in OOHC have poorer life outcomes than other children' (FACSIA, 2010).…”
Section: Residential Care In Australiamentioning
confidence: 99%
“…Many authors also comment, that along with the stresses and strains felt by care givers and workers in the OOHC system and the poor attention paid to OOHC politically and academically, the national data indicates that we are continuing to fail to halt the rise of children coming into care, the rise in placement breakdown, poor reunification rates, poor educational outcomes, and the poor social and emotional health and wellbeing of children in care (Barber, 2001;Carter, 2004;Cashmore, Paxman, & Townsend, 2007). The National Standards for OOHC: Consultation Paper (2010) states that it is 'widely reported that children who have been placed in OOHC have poorer life outcomes than other children' (FACSIA, 2010).…”
Section: Residential Care In Australiamentioning
confidence: 99%
“…But the experience of disrupted schooling makes this difficult and usually means they lag academically behind their classroom peers. This, along with many other barriers they face, makes them susceptible to early leaving (Cashmore and Paxman, 1996, 2006, 2007Cashmore, Paxman and Townsend, 2007;Montserrat, Casas and Malo, 2013). Making the children aware of the benefits of education and the options available to them is, therefore, a crucial aspect of motivational behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Several research studies, however, have investigated the educational outcomes of this cohort. The majority of these studies have focused on school level education and found that students in care experience numerous educational challenges and disruptions at school (Tilbury, 2010;Wise, Pollock, Mitchell, Argus, & Farquhar, 2010), are significantly behind their peers academically (Australian Institute of Health and Welfare, 2007Welfare, , 2011 and are less likely to complete secondary school (Cashmore, Paxman, & Townsend, 2007;Townsend, 2012). In 2013, the AIHW proposed a national methodology for the collection and reporting of the educational outcomes of young people in care up to 17 years of age (Australian Institute of Health and Welfare, 2013b).…”
Section: Out-of-home Carementioning
confidence: 99%